The Burial Sites of Sheikh Siti Jenar: Social Change and the Creation of Tombs and Memorial Spaces in Java - Jati Pamungkas; Taufik Alamin; Asyari; Hamdani Bika (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2026)
This study examines the claim burial sites of Sheikh Siti Jenar, a mysterious figure in Javanese history, analyzed from the perspective of social structure and collective memory from Javanese. The importance of this research is the fact from the narrative of Sheikh Siti Jenar continues to shape religious authority, pilgrimage patterns, and understandings of Islamic history. Using a qualitative, this study combines analysis of historical documents, ethnographic observation, and semi-structured interviews with local communities, custodians of sites, and religious leaders about the burial sites of Sheikh Siti Jenar. The results demonstrate that the distribution of Siti Jenar's burial sites is not simply a historically contested phenomenon, but rather a socially constructed reality that emerges from tensions related to religious authority, local cultural traditions, politics, and economics within the pilgrimage tradition. The tombs function simultaneously as centers of spiritual power and sites where historical meanings are continually forged and contested. The study finds that sacred spaces in Java are subject to change, social (not historical) productions, and calls for more critical and inclusive methods in the preservation and interpretation of Islamic sites, particularly sacred tombs, to allow for the coexistence of different narratives.